The development of nationalism in Syria from the late Ottoman period until march 2011 and the impact of the uprising on nationalism - Fattahi, Tariq (My University, 2022)
Ortadoğu’da milliyetçilik meselesi, önemli tartışmaların ve ihtilafların konusu olmaya devam etmektedir. Osmanlı İmparatorluğu’nun çöküşü ve ardından gelen sömürge dönemi, bu bölge halkları arasında milliyetçi çekişmelere elverişli bir ortam oluşturdu. Suriye örneği de bir istisna oluşturmamaktadır. Bu araştırma projesi iki bölümden oluşmaktadır. İlk bölüm, Miroslav Hroch’un milliyetçiliğin üç evreli gelişimi üzerinden Suriye’deki milliyetçi düşüncenin gelişiminin geç Osmanlı döneminden Mart 2011 ayaklanmasının arifesine kadar izini sürmektedir. İkinci bölümde ise, Mart 2011 ayaklanmasının milliyetçiliği nasıl etkilediği incelenmektedir. Çalışmanın ana argümanı, ayaklanmanın duygusal bir topluluğun, başka bir deyişle belirli bir olay sonunda kolektif bir duygusallıkla bir araya gelen siyasi bir topluluğun oluşmasına yol açtığı gerçeğidir. Ancak, çatışmanın militarizasyonu, Suriye rejiminin bölücü stratejisi ve siyasi muhalefetin yetersiz performansı, bu duygusal topluluğun tam teşekküllü bir milliyetçi harekete dönüşmesini engellemiştir ve sonunda milliyetçilik meselesinin çeşitli siyasi aktörler arasında ademi merkezileşmesine yol açmıştır.

Contents LIST OF GRAPHICSx INTRODUCTION1 CHAPTER 1 REVIEW OF THE LITERATURE ON NATIONS AND NATIONALISM7 1.1 Primordialism7 1.2 Modernism9 1.2.1 Economic Transformation10 1.2.2 Political Transformations11 1.2.3 Social/ cultural transformations14 1.4 Miroslav Hroch’s Three Phases of Nationalism15 1.5 Emma Hutchison’s Affective Communities16 1.6 Conclusion16 CHAPTER 2 THE DEVELOPMENT OF NATIONAL IDENTITY IN SYRIA FROM THE LATE OTTOMAN PERIOD UNTIL THE 2011 UPRISING20 2.1 Early Nationalist thought in Syria20 2.1.1 Early Imaginations of Syrian Nationalism21 2.1.2 Early Syrian/ Arab nationalist though as rooted in Islamic Modernism23 2.2 The Committee of Union and Progress Era, World War I and Collapse of the Ottoman State26 2.3 The Impact of French Colonialism on Nationalism in Syria31 2.4 Nationalism in Syria in the post-independence Era34 2.4.1 the Nationalism of Greater Syria34 2.4.2 The Baath Party and Secular Arab Nationalism36 2.4.3 Islam-based Arab Nationalism37 2.5 Nationalism in Syria During the Baath Party Era38 2.5.1 The Intra-Baath Confrontation38 2.5.2 The Baath Party vs The Muslim Brotherhood39 2.5.3 Nationalism in Syria under Hafez Al-Assad’s Rule (1970 – 2000)41 2.5.4 Nationalism in Syria under Bashar Al-Assad (2000 – 2011)43 2.6 Conclusion45 CHAPTER 3 THE SYRIAN UPRISING AND CONFLICT48 3.1 Examining the root causes of the Syrian conflict48 3.1.1 Political Factors48 3.1.2 Economic Factors51 3.1.2 Social Factors52 3.2 The Initial Demonstrations and Descent into Conflict53 3.3 The Regime’s Strategy to Suppress the Uprising55 3.4 External Intervention and the Division of the country into four main spheres of influence59 3.4.1 Turkey59 3.4.2 United States of America60 3.4.3 Iran61 3.4.4 Russia62 Conclusion64 Chapter 4: THE IMPACT OF THE UPRISING ON NATIONALISM IN SYRIA65 4.1 Introduction:65 4.2 The Uprising as an Affective Community:66 4.3 Examining the Uprising’s Slogans70 4.3.1 Betrayal70 4.3.2 Defiance71 4.3.3 Solidarity71 4.3.4 Unity72 3.3.5 Freedom73 4.4 Examining the Weekly Demonstration Titles73 4.5 The Failure of the Uprising as an Affective Community78 4.5.1 Militarization of the Protest Movement78 4.5.2 The Regime’s Divisive Strategy80 4.5.3 The Failure of the Political Opposition81 4.6 Competing Visions for National Identity83 4.6.1 The Syrian Islamic Council and Islam-based Arab Nationalism84 4.6.2 The Syrian Nationalism Declaration85 4.6.3 The regime’s Unchanged Vision86 4.6.4 The Syrian Democratic Council and the Popular Will Party87 4.7 Conclusion:87 CONCLUSION91 BIBLIOGRAPHY97
Keywords: Middle East; Milliyetçilik; National Identity; Nationalism; Orta Doğu; Syria